Efektivitas E-Lapor Dalam Upaya Peningkatan Kualitas Pelayana Di Diskominfo Kabupaten Bandung - Syifa Nurul Rahima; Sendi Hinaya; Sofia Nur Kholidah (PRAJA: Jurnal Ilmiah Pemerintahan, 2022)
The application of the E-LAPOR application is a forum to convey development aspirations or complaints from the community regarding the problems that are being felt and to increase two-way interaction between the community and the government in overseeing development programs. The purpose of this study is to analyze how the effectiveness of the application of E-LAPOR in the management of public service complaints in Bandung Regency. This study uses the theory of effectiveness according to Sutrisno who suggests that there are four variables that affect organizational effectiveness, environmental characteristics, characteristics and policies of management practices. This study uses descriptive qualitative research methods and data analysis techniques used are the Miles and Huberman models which include data reduction, data presentation, and drawing conclusions. The results of the study indicate that the application of the E-LAPOR application in Bandung Regency makes it easier for the public to submit complaints or reports on problems or issues in government agencies that are being felt. However, in its implementation it is not effective, seeing that there are still problems that occur. The suggestion given by the researcher is that the monitoring system needs to be developed again, such as making a new feature where Diskominfo can unify the follow-up of complaints or problems from the community to the realization stage.